Mapping Doctoral Research in Library and Information Science in India, 1950-2023. 2V. Vol. 1: Inventory of Doctoral Dissertations. Vol. 2: Appendices and Indices to Inventory of Doctoral Dissertations. Singh, Shashi Prabha and Babbar, Parveen. Synergy Books India: New Delhi, 2024 - Sharma, Jaideep (Journal of Information and Knowledge, 2024)
No Abstract.